Profesionalisme Guru Dalam Pendidikan Islam dan Gambaran Ideal Seorang Pendidik - Khusnan Iskandar (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
This article explores about the professionality of teacher in Islamic perspective. As long as we know, the professional teachers play a major role in educational process as whole. In Islam, professional teachers lead a double mission (religion and knowledge) at the same time. This illustrates that teaching is hard and it requires someone professional. Professionalism means that every job should be done by someone professional. To be considered as professional, teachers must have at least two important things. They are dedication and professionalism. Islam itself very concerns to professionalism. It means that everything must be done by the experts. As the doer of professional behavior, teachers should be characterized by dignity or integrity or ethics. The characteristics possessed by the teachers will reflect themselves. Also, their character will be integrated as their personality. Keywords; Professionalism, Islamic Education, Teacher